Dapagliflozin in Patients with Chronic Heart Failure: A Systematic Review and Meta-Analysis - Ru-ping Cai; Yu-li Xu; Qiang Su (Cardiology Research and Practice)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors represent newly developed oral antidiabetic drugs that are practiced for type 2 diabetes mellitus management and may decrease the risk of the first hospitalization in heart failure. The activity of SGLT2 inhibitors is not related to glucose, and the effectiveness and safety of SGLT2 inhibitors in individuals with chronic heart failure (CHF) remain unclear. We systematically retrieved PubMed, Cochrane Library, Embase, NCKI, VIP, Wanfang Data, and ClinicalTrials.gov records to identify eligible trials. The primary endpoints were cardiovascular death/hospitalization for heart failure (CV death/HHF), cardiovascular death, and hospitalization for heart failure. Secondary endpoints included hypoglycemia, volume depletion, urinary tract infection, left ventricular ejection fraction (LVEF), and NT-proBNP. Nine randomized controlled clinical trials were included. Dapagliflozin was reported to significantly decrease CV death/HHF (relative risk (RR): 0.75; 95% confidence interval (CI): 0.68–0.84), CV death (RR: 0.80; 95% CI: 0.68–0.93), and HHF (RR: 0.72; 95% CI: 0.63–0.83). There was no effect on hypoglycemia (RR: 0.69; 95% CI: 0.34–1.40), volume depletion (RR: 1.17; 95% CI: 0.97–1.41), urinary tract infection (RR: 0.82; 95% CI: 0.43–1.57), LVEF (WMD: 0.53; 95% CI: −4.04–5.09), or NT-proBNP (SMD: −0.66; 95% CI: −1.42–0.10). The risk of CV death/HHF, CV death, and HHF was lower among patients receiving dapagliflozin than patients receiving placebo.